Diagnosis and remediation of physics students’ difficulty through the outdoor student remediation teaching (OSRT) - Muslimin, Muslimin; Makitulung, Janli Novrenli; Werdhiana, I Komang; Nurlaila, Nurlaila; Agustina, Agustina (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
The study's purpose was to describe students' learning difficulties in physics, the causes of students' learning difficulties in physics, and the remediation to solve students' difficulties. This research was exploratory research with qualitative and quantitative approaches. The populations of this study were eleventh-grade students of SMAN 6 Palu. The respondents were chosen based on the lowest posttest results. The research instruments were OSRT treatment, pretest, posttest, and diagnostic test. The data were analyzed by comparing the pretest results, the posttest, and the gain score to determine the improvement after the remediation. Respondent A obtained 0.71 within the high category, respondent B obtained 0.69 within the high category, respondent C obtained 0.85 within the high category, respondent D obtained 0.84 within the high category, and respondent E obtained 0.46 within the moderate category. It can be concluded that internal and external factors caused difficulties. The internal factors were students' weak basic knowledge and weak material prerequisites, while the external factors were the teacher's learning methods that did not attract students' attention. The OSRT can overcome the difficulty in understanding Newton's law's concept to improve their ability to understand physics concepts.